Northern Goshawk, Accipiter gentilis (New Jersey Department of Environmental Protection (NJDEP), Division of Fish and Wildlife, 2000)
This fact sheet contains information about the Northern Goshawk, the largest of the three North American accipiters, or forest hawks that nest in mature, contiguous forests that are safeguarded from human activity and development.